URGENCY OF CONTENT VILLAGE REGULATION IN THE FRAMEWORK OF VILLAGE GOVERNANCE - Ali Rido (Indonesian Journal of Law and Policy Studies, 2020)
Village regulations, as part of the rules, must-have content material if they are to be established. In higher standards, the content of village regulations is not explicitly regulated but only explains the macro aspects of village authority. Given that the content material is not in detail, it is essential to reinforce the content of village regulations as a guide in its formation. Through normative juridical research that uses a statutory and conceptual approach, the results found two critical things. First, affirming the content of village regulations is very important considering that the village government regime has the authority to form village regulations, which are a type of statutory provision as is familiar with other laws and regulations. Second, the content of village regulations can be emphasized and detailed by looking at the authority of the village. Thus, the content materials that can be used as guidelines in the formation of village regulations are as follows: 1). The content relating to the rights of origin of the village; 2). Material content about the value of local communities; 3). The contents of which are the duties of the government following the provisions of laws and regulations.